THE INFLUENCE OF ORGANIZATIONAL STRUCTURE, LEADERSHIP STYLE, MANAGEMENT CONTROL SYSTEMS, AND ORGANIZATIONAL CULTURE TOWARD BEHAVIOUR DECISION MAKING - Deborah Christin Darmawan; Suwignyo Widagdo; Hamzah Fansuri Yusuf (MBA - Journal of Management and Business Aplication, 2020)
This research aims to know the influence of organizational structure, leadership style,management control systems, and organizational culture toward behaviour decision making.Data collection methods used in this research is a method of questionnaire. The results of thisstudy suggest that the organizational structure of partially against the influential behavioraldecision making, leadership styles partially against the influential behavioral decisionmaking, not management control systems influential partially against the behavior ofdecision-making, and organizational culture has no effect partially against the decisionmaking behavior. Research results also showed a simultaneous influence organizationalstructure, leadership style, management control systems, and organizational culture towardsdecision-making behavior and note that the value of the coefficient of determination60.3%, while the remaining 39.7% is explained by other factors that are not described in thismodel.